Analisis Kualitas Layanan Aplikasi ASN-G Kabupaten Tangerang Dengan Metode Servqual - Muhammad Ridwan Maulana; Qori Halimatul Hidayah (Ikatan Ahli Informatika Indonesia, 2025)
This study aims to evaluate the quality of the ASN-G (Aparatur Sipil Negara Gemilang) application service used by the Tangerang Regency Housing, Settlement, and Cemetery Agency using the SERVQUAL method. The five main dimensions of service quality analyzed include Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Data collection was conducted through the distribution of an online questionnaire using Google Forms to 60 civil servants as respondents, and the data was analyzed descriptively using SPSS software for validity and reliability testing of the instrument. The results of the study indicate that all dimensions have a negative gap with an average gap of -0.5927, indicating that the application's performance has not been able to meet user expectations. The most problematic dimensions are Empathy (gap -0.753) and Responsiveness (gap -0.6467), with the weakest attributes being device compatibility (TA_4), guidance for new users (EM_3, gap -1.20), and application performance consistency (RE_1, gap -1.13). The main identified barriers are technical issues such as connection timeouts (reported by 37% of respondents) and insufficient guidance for older users (43.33% of respondents are over 50 years old). Based on these findings, immediate improvements are needed in the application's user interface, system response speed, and the provision of more adaptive technical support. Strategic recommendations include adding interactive video-based or icon-based guidance.